KESADARAN LINGKUNGAN DAN UPACARA GREBEG DI MAKAM SUNAN KALIJAGA - Purwadi Purwadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
This article discusses the traditional ceremony which is conductedto the natural harmony. The aim of this paper is firstly, to reveal the conceptwhich is constructed in traditional ceremony which is inherited bySunan Kalijaga. Secondly, it also discusses the cosmic awareness inJavanese spirituality. It is found that the environmental harmony conceptin traditional ceremony in Sunan Kalijaga’s tomb has a local wisdom andvirtues that need to be preserved. The cosmic awareness which is built bySunan Kalijaga in the spreading of Islam is taking the local virtues andtransforming them into Islamic teaching.